Silver treasures from the land of Sheba : regional Yemeni jewelry - Ransom, Marjorie; Liu, Robert K. (Cairo, Egypt ; New York : The American University in Cairo Press, 2014)
This book documents a disappearing artistic and cultural tradition with over three hundred photographs showing individual pieces, rare images of women wearing their jewelry with traditional dress, and the various regions in Yemen where the author did her field research. Ransom's descriptions of the people she met and befriended, and her exploration of the significance of a woman's handmade jewelry with its attributes of power, protection, beauty, and personal identity, are a rich source of information that will appeal to ethnic jewelry fans, ethnographers, jewelry designers, and art historians. Amulet cases, hair ornaments, bridal headdresses, earrings, necklaces, ankle and wrist bracelets are all beautifully photographed in intricate detail, interspersed with the author's own photographs of the women who shared their stories and their hospitality with her.
Includes bibliographical references and index.
Keywords: Silver jewelry -- Yemen (Republic); Yemenis -- Clothing